Advances in the Immunology and Genetics of Leprosy - Mi, Zihao; Liu, Hong; Zhang, Furen (Frontiers in Immunology, 2020)
Leprosy, a chronic intracellular infectious skin disease, has affected humans for more than 1000 years and is a stigmatized disease even now. Since clinical manifestations of leprosy patients present as an immune-related spectrum, leprosy is regarded as an ideal model for studying the interaction between host immune response and infection; in fact, the landscape of leprosy immune responses has been extensively investigated. Meanwhile, leprosy is to some extent a genetic disease because the genetic factors of hosts have long been considered major contributors to this disease. Many immune-related genes have been discovered to be associated with leprosy. However, immunological and genetic findings have rarely been studied and discussed together, and as a result, the effects of gene variants on leprosy immune responses and the molecular mechanisms of leprosy pathogenesis are largely unknown. In this context, we summarized advances in both the immunology and genetics of leprosy and discussed the perspective of the combination of immunological and genetic approaches in studying the molecular mechanism of leprosy pathogenesis. In our opinion, the integrating of immunological and genetic approaches in the future may be promising to elucidate the the molecular mechanism of leprosy onset and how leprosy develop into different polar forms.